Analisis Perbandingan Sistem Penuntutan: Perbandingan Hukum dari Amerika Serikat dan Negara-negara Eropa - Orzhynska, Elvira; Rarytska, Viktoria; Stoianov, Konstiantyn; Dontsov, Denys; Terletskii, Anatoliy (Universitas Islam Negeri Antasari Banjarmasin, 2024)
This research used a qualitative approach with a focus on comparative studies and document analysis. The approach was designed to explore the legal regulations and organizational systems of prosecutors' offices in the United States, European countries, and Ukraine. Data were collected through a literature review of relevant constitutions, laws, and other official documents, such as reports from international organizations, court decisions, and prosecutorial codes of ethics. The analysis was conducted using a comparative method, whereby prosecutorial systems from different countries were compared based on several key criteria. These criteria included organizational structure, level of independence, legal authority, and efficiency of human resources and funding. This approach enabled the identification of best practices that could be applied to address local challenges in Ukraine. Data were analyzed thematically to identify patterns, differences, and similarities among the prosecutorial systems studied. For example, decentralized systems in the United States were compared with centralized models in Germany and France to assess their implications for case management effectiveness. The analysis also included an evaluation of the prosecutor's ability to handle specialized cases, such as war crimes investigations, as well as integration with applicable international standards. As a final step, the research validated the findings through source triangulation to ensure the accuracy and credibility of the data. This approach provided a solid basis for developing recommendations for reforming the prosecutorial system in Ukraine oriented towards the principles of the rule of law, protection of human rights, and operational effectiveness.